Neuromuscular function and fatigue resistance of the plantar flexors following short-term cycling endurance training - Behrens, Martin; Weippert, Matthias; Wassermann, Franziska; Bader, Rainer; Bruhn, Sven; Mau-Moeller, Anett (Frontiers in Physiology, 2015)
Previously published studies on the effect of short-term endurance training on the neuromuscular function of the plantar flexors have shown that the H-reflex elicited at rest and during weak voluntary contractions was increased following the training regime. However, these studies did not test H-reflex modulation during isometric maximum voluntary contraction (iMVC) and did not incorporate a control group in their study design to compare the results of the endurance training group to individuals without the endurance training stimulus. Therefore, this randomized controlled study was directed to investigate the neuromuscular function of the plantar flexors at rest and during iMVC before and after eight weeks of cycling endurance training. Twenty-two young adults were randomly assigned to an intervention group and a control group. During neuromuscular testing, rate of torque development, isometric maximum voluntary torque and muscle activation were measured. Triceps surae muscle activation and tibialis anterior muscle co-activation were assessed by normalized root mean square of the EMG signal during the initial phase of contraction (0-100, 100-200 ms) and isometric maximum voluntary contraction of the plantar flexors. Furthermore, evoked spinal reflex responses of the soleus muscle (H-reflex evoked at rest and during iMVC, V-wave), peak twitch torques induced by electrical stimulation of the posterior tibial nerve at rest and fatigue resistance were evaluated. The results indicate that the endurance training did not lead to a significant change in any variable of interest. Data of the present study conflict with the outcome of previously published studies that have found an increase in H-reflex excitability after endurance training. However, these studies had not included a control group in their study design as was the case here. It is concluded that short-term cycling endurance training does not necessarily enhance H-reflex responses and fatigue resistance.